The Failed Conversion of CareFirst BlueCross BlueShield to For-Profit Status: Part 1, the Whole Story - Bruce Mcpherson (SAGE Publishing, 2004)
This article presents in detail the relevant facts surrounding CareFirst's failed attempt to convert to for-profit status and be acquired by the for-profit company, Wellpoint Health Networks, Inc. It chronicles events and describes the political environment leading up to the Maryland insurance commissioner's review of the application, the review process and roles played by various stakeholders and the media, the commissioner's decision and rationale, and the aftermath of actions and reactions by various parties, including state legislation to reform CareFirst. This case study was based on interviews with several key players, as well as a review of numerous newspaper articles and the wealth of documents prepared for, and emanating from the review process. Providing an in-depth look at the missteps by CareFirst's board and executives, this article sets the stage for a second one translating these details into lessons for other states and for all types of nonprofit health care organizations involved in any kind of strategic decision making that affects the public interest.